Pemberdayaan dan pendampingan desa digital melalui media website pada Desa Kadubungbang-Pandeglang - Muhamad As’adi; Akhmad Nidhomus Zaman; Alina Cynthia Dewi; Najibatul Mujahidah; Angger Ridho Safaat; Ihda Amalina; Adella Nuha A; Pama Shandyasta; Bryan Siburian; Claudia Ivana S (Unri Conference Series: Community Engagement, 2021)
Kadubungbang Village is located in the Pulosari Mountains area which stretches from west to south. This village is the place for PKM 2021 as a follow-up to PKM Mandiri 2020 (installation of barcode posters from the digital village android application). By the targets and plans of the Ministry of Villages, PDT, and Transmigration 2020 which aims to equalize Digital Villages in all villages in Indonesia. The method of activity is carried out by conducting a preliminary study, namely coordination with the urban village and field surveys at each tourist spot. Next is the creation of a website that previously had an application model that was converted to the jelajahdesa.com website. Then for the technical socialization by exploring tourist attractions and interviewing each tourist spot, socializing with village staff and representatives of tourist attractions, and updating banners containing barcodes and webs at each tourist spot. The results achieved from this activity, namely the understanding of the training participants on the operation of the website and indirectly attracting visitors to be able to expose the potential of the village and make the villagers more creative to build the village economy.